This Bright Light of Ours : Stories from the Voting Rights Fight - Gitin, Maria (Book collections on Project MUSE., 2014)
"This Bright Light of Ours combines a memoir with oral history to create a very vivid portrait of the Freedom Summer of 1965 in Wilcox County, Alabama, when volunteers and long-standing local black leaders were shaking the cultural norms, registering thousands of new voters. This book documents the first-person experience of Maria Gitin, an idealistic 18-year-old college freshman from San Francisco who felt called to action when she viewed televised images of the brutal treatment of peaceful demonstrators during what became known as Bloody Sunday in Selma, Alabama"--